Making literacy functional in rural West Africa: The experience of Groupements villageois in Burkina Faso - Peter A. Easton; Paul T. Ilboudo; Mwenene Mukweso (Adult Education Research Conference, 1994)
This paper examines the results of an innovative functional literacy program in rural Burkina Faso which gives accelerated training to village enterprise managers.